OPTIMAL APPROACHES AND RESOURCES FOR IMPARTING INSTRUCTIONAL CONTENT IN ENGLISH LANGUAGE EDUCATION - Yuldasheva , Kamola Eldor qizi (Educational Research in Universal Sciences, 2023)
English Language Teaching (ELT) has undergone significant transformations in recent years, owing to advancements in technology, changing learner preferences, and evolving teaching methodologies. In this digital age, educators are presented with a plethora of opportunities to enhance the delivery of instructional content to English language learners. This article explores some of the optimal approaches and resources that can be employed to achieve effective English language education.